Ketones for Post-exercise Recovery: Potential Applications and Mechanisms - Mansor, Latt Shahril; Woo, Geoffrey Hubert (Frontiers in Physiology, 2021)
Ketogenic diet has been introduced in therapeutic areas for more than a century but the role of ketones in exercise performance has only been explored in the past decade. One of the main reasons that allows the investigation of the role of ketones in exercise performance is the emergence of exogenous ketones, allowing athletes to achieve the state of ketosis acutely, and independent of their metabolic states. While there are mixed results showing either exogenous ketones improve exercise performance or no effect, the mechanisms of action are still being heavily researched. Moreover, these early data from exercise physiology studies suggested that exogenous ketones may play a more prominent role in exercise recovery, leading to a more pronounced cumulative impact over subsequent exercise performance. This review will look at existing evidence on the role of ketones in recovery and attempt to identify the current best practices and potential mechanisms that drive improved recovery.